Neurocritical care monitoring of encephalopathic children with acute liver failure: A systematic review. (13th August 2019) - Hunt, Adam; Tasker, Robert C.; Deep, Akash
Abstract: Research on non‐invasive neuromonitoring specific to PALF is limited. This systematic review identifies and synthesis the existing literature on non‐invasive approaches to monitoring for neurological sequelae in patients with PALF. A series of literature searches were performed to identify all publications pertaining to five different non‐invasive neuromonitoring modalities, in line with PRISMA guidelines. Each modality was selected on the basis of its potential for direct or indirect measurement of cerebral perfusion; studies on electroencephalographic monitoring were therefore not sought. Data were recorded on study design, patient population, comparator groups, and outcomes. A preponderance of observational studies was observed, most with a small sample size. Few incorporated direct comparisons of different modalities; in particular, comparison to invasive intracranial pressure monitoring was largely lacking. The integration of current evidence is considered in the context of the clinically significant distinctions between pediatric and adult ALF, as well as the implications for planning of future investigations to best support the evidence‐based clinical care of these patients.